Witches of Brooklyn. 4, Spell of a time - Escabasse, Sophie (Escabasse, Sophie. Witches of Brooklyn, 2023)
"A trip to Coney Island to pick up trash goes sideways when Effie and Garance learn that there is a missing...mermaid?! Every time Effie thinks she finally has this magic life down, something new pops up! But this time, with the help of Garance, some talkative seagulls, and a rather helpful turtle, Effie is going to save the day and find this mermaid!" --